Green subsidies as strategic trade policy tools - Domenico Buccella; Luciano Fanti; Luca Gori (Global Labor Organization (GLO), 2023)
In a three-country model in which export countries adopt environmental policies, this note analyses how abatement ("green") subsidy can become a potential strategic trade policy tool. When governments set the optimal policy tool considering their local environmental damages, a rich set of equilibria arise. In contrast to the standard result, it is shown that subsidising pollution abatement can 1) emerge as a Pareto-efficient equilibrium of the game; and 2) be the only feasible environmental policy when environmental awareness is low, irrespective of the technological efficiency. Therefore, "green" subsidies can lead to a win-win situation.
Keywords: H23; F13; L13; 330; Abatement subsidy; Exports; International duopoly